Pendampingan pembuatan herbal instan temulawak bagi ibu-ibu UMKM jamu di daerah pesisir pantai Kenjeran - Faizah, Ana Khusnul; Praditapuspa, Ersanda Nurma; Nurrahman, Nani Wijayanti Dyah; Kurniawan, Wishnu (Universitas Mataram, 2024)
The community is focusing on health drinks which can be utilised as health drinks to achieve community health. However, a number of issues were discovered in partners who produced herbal beverage preparations; as these preparations lack preservatives, they don't survive enough. Making fast herbal preparations that have the same qualities as traditional herbal preparations would help them last longer without sacrificing taste or convenience for users. Partners created instant herbal preparations, examined the flow qualities and flow content, and gained a better understanding of how to produce instant herbs and high-quality herbal medicine as a result of this work.